Analysis of Strategic Management for Local Layer Agribusiness Development in North Sulawesi - Jolyanis Lainawa; Tilly Flora Desaly Lumy; Jolanda. K.J. Kalangi (AIBPM Publisher, 2022)
The strategy for developing local layer agribusiness in North Sulawesi addresses the gap between growing consumption needs and limited product availability. The purpose of this research is to conduct a business feasibility study and formulate a strategy for local layer business development in North Sulawesi. The result of the research states that the development strategy priorities include partnership patterns, fostering human resources (HR) breeders in an integrated manner, encouraging investment growth, increasing the productivity of local layer businesses in rural areas, improving genetic quality, developing culinary businesses, creating production facilities, encouraging the rise of local layer SMEs in the countryside, encouraging the development of science technology and digitization of local layer cultivation in rural areas, vaccination programs, and utilizing unused land for the development of intensification of chicken farming in rural areas.